Guidance Note on Post Program Monitoring. (Policy Papers; Policy Paper, 2017)
operational guidance to staff on the implementation of post-program monitoring (PPM). It is based on the policy paper Strengthening the Framework for Post-Program Monitoring and the related Board discussion and summing-up, and supersedes the guidance note issued in March 2010.